(untitled) (Menara Perkebunan, 2016)
Abstract The use of the appropriate source of nodal bud explants in culture can increase the effectiveness and efficiency of shoot multiplication. An experiment was conducted to determine and compare the rate of in vitro shoot multiplication from apical and axillary buds in cinchona (Cinchona ledgeriana Moens) and their subsequent growth and development. The plant material used was Cinchona ledgeriana originating from the Indonesian Tea and Cinchona Research Institute, Gambung, West Java. Explants were taken from apical and axillary nodes from in vitro germinated seedlings. The cultures were incubated at 26 0 C and 60% relative humidity under a 14-h photoperiod with light intensity of 30 µmol photon/m 2 /sec. provided by cool-white fluorescent tubes (TL 40 W) for 4 - 8 weeks. The parameters observed were shoot multiplication rate, shoot growth and development such as shoot length, leaf number and rooting frequency. Apical and axillary nodes produced shoots at different multiplication rates on Murashige-Skoog (MS) standard medium containing 30 g/L sucrose and supplemented with 1 – 5 mg/L BA in combination with 0.1 mg/L IBA. Furthermore, shoots or plantlets of cinchona grew and developed on the same media containing 5 – 10 mg/L IAA combined with 0.5 mg/L IBA. The results showed that shoot multiplication rate was higher in axillary than in apical nodes. The highest multiplication rate in axillary nodes was 24.6 shootlets with 3 mg/L BA treatment, whereas in apical nodes it was 17.2 shootlets with 5 mg/L BA treatment for eight weeks. The highest rooting frequency of cinchona plantlet was 90%, achieved with 5 mg/L IAA in combination with 0.5 mg/L IBA. The plantlets were successfully acclimatized and transplanted to the field Abstrak Sumber eksplan berupa nodus/tunas pada kultur in vitro umum digunakan untuk multi- plikasi tunas. Penelitian ini bertujuan untuk membandingkan tingkat multiplikasi antara tunas apikal dengan tunas aksiler tanaman kina Ledger secara in vitro. Bahan tanaman yang digunakan adalah kina Ledger (Cinchona ledgeriana Moens) yang berasal dari Pusat Penelitian Teh dan Kina, Gambung, Jawa Barat. Eksplan berupa nodus/ tunas apikal dan aksiler asal biji yang dikecam- bahkan secara in vitro. Kultur tersebut diinku- basikan dalam ruang terang pada intensitas cahaya 30 μmol foton/m 2 /detik dengan periode penyinaran 14 jam pada suhu 26 0 C dan kelembaban relatif + 60% selama 4 – 8 minggu. Parameter yang diamati adalah perbandingan multiplikasi tunas dan pertumbuhan tunas yang meliputi rata-rata tinggi tunas, jumlah daun dan frekuensi pengakaran. Nodus apikal maupun aksiler menghasilkan tunas dengan tingkat Murashige-Skoog (MS) standar yang me- ngandung sukrosa30 g/L dan ditambahkan BA 1 – 5 mg/L dikombinasikan IBA 0,1 mg/L. Selanjutnya tunas/planlet kina tersebut berhasil tumbuhdan berkembang pada medium sama yang diberi IAA 5 – 10 mg/L dikombinasikan dengan IBA 0,5 mg/L. Hasil penelitian menunjukkan bahwa tingkat multiplikasi tunas aksiler lebih tinggi dari pada tunas apikal. Multiplikasi tunas aksiler menghasilkan jumlah tunas rata-rata tertinggi sebesar 24,6 tunas per eksplan pada perlakuan BA 3 mg/L sedangkan multiplikasi tunas apikal tertinggi sebesar 17,2 tunas per eksplan pada perlakuan BA 5 mg/L pada umur delapan minggu. Frekuensi pengakaran planlet kina tertinggi mencapai 90% pada perlakuan IAA 10 mg/L yang dikombinasikan dengan IBA 0,5 mg/L. Planlet yang dihasilkan telah berhasil diaklimatisasi dan dipindahkan ke tempat persemaian lapang.